2014
DOI: 10.1063/1.4863558
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ordering of water at hydrophobic surfaces

Abstract: We study the properties of water molecules adjacent to a hydrophobic molecular layer with vibrational sum-frequency generation spectroscopy. We find that the water molecules at D2O/hexane, D2O/heptane, and D2O/polydimethylsiloxane interfaces show an enhanced ordering and stronger hydrogen-bond interactions than the water molecules at a D2O/air interface. With increasing temperature (up to 80 °C) the water structure becomes significantly less ordered and the hydrogen bonds become weaker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
163
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(180 citation statements)
references
References 33 publications
14
163
0
2
Order By: Relevance
“…Above 2670 cm −1 one expects to find water molecules with a single or no H-bond donors [27]. As an example, the dangling OD bond vibrates at 2745 cm −1 [11]. Figure 2 shows SFS spectra in PPP (A) and SSP (B) polarization combination for different pD values.…”
Section: Spectral Characterization Of the Surface Regionmentioning
confidence: 96%
See 2 more Smart Citations
“…Above 2670 cm −1 one expects to find water molecules with a single or no H-bond donors [27]. As an example, the dangling OD bond vibrates at 2745 cm −1 [11]. Figure 2 shows SFS spectra in PPP (A) and SSP (B) polarization combination for different pD values.…”
Section: Spectral Characterization Of the Surface Regionmentioning
confidence: 96%
“…The Richmond lab [8][9][10] has investigated planar water/CCl 4 and water/alkane systems and concluded that the hydrogen bonds between water molecules at these interfaces are significantly weaker than at the air/water interface. Bakker and coworkers however, found from SFG studies on the same systems that the ordering of hydrogen bonded water molecules is rather enhanced [11]. Thus, few experimental studies have been performed to elucidate the water structure at the hydrophobic/liquid water interface, and from these it appears that the surface structure of water is not yet very well defined.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…X-ray absorption spectroscopy and xray Raman scattering demonstrated that water, consists of structures with two strong H-bonds, one donating and one accepting, thus promoting formation of chain-like structures [22][23][24]. There is much theoretical and experimental evidence that water molecules are strongly oriented in the vicinity of hydrophobic moieties [25][26][27], and this is the case in our treatment (recall, that we restricted our consideration by sessile …”
Section: Contribution Into the Line Tensionmentioning
confidence: 77%
“…For the estimation of the entropic input into the line tension the threephase line is approximated by a polymer chain. This approximation is approximated by novel experimental data indicating strong orientation effects for liquid molecules located in the vicinity of hydrophobic moieties [22][23][24][25][26][27]. Thus, the polymer-chain model may be successful for sessile droplets placed on hydrophobic (say polymer) solid substrates.…”
Section: Resultsmentioning
confidence: 99%